Mycoketide: A CD1c-Presented Antigen with Important Implications in Mycobacterial Infection - Isamu Matsunaga; Masahiko Sugita (Clinical and Developmental Immunology)
Mycobacterium tuberculosis and related mycobacteria species are unique in that the acid-fast bacilli possess a highly lipid-rich cell wall that not simply confers resistance to treatment with acid alcohol, but also controls their survival and virulence. It has recently been established that a fraction of the cell wall lipid components of mycobacteria can function as antigens targeted by the acquired immunity of the host. Human group 1 CD1 molecules (CD1a, CD1b, and CD1c) bind a pool of lipid antigens expressed by mycobacteria and present them to specific T cells, thereby mediating an effective pathway for host defense against tuberculosis. The contrasting and mutually complementary functions of CD1a and CD1b molecules in terms of the repertoire of antigens they bind have been well appreciated, but it remains to be established how CD1c may play a unique role. Nevertheless, recent advances in our understanding of the CD1c structure as well as the biosynthetic pathway of a CD1c-presented antigen, mannose-1, β-phosphomycoketide, expressed by pathogenic mycobacteria now unravel a new aspect of the group 1 CD1 biology that has not been appreciated in previous studies of CD1a and CD1b molecules.